(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
This article analyzes the importance of pedagogical conditions in the development of professional skills of future engineer-technologists. In order to strengthen the professional knowledge and practical skills of students, it is important to use innovative methods, practical training and modern technologies in the educational process. The importance of using personal development, teamwork and leadership skills is also emphasized. Pedagogical conditions help prepare students as highly qualified specialists in a changing technological environment.